Fifty years of LIS education in Sri Lanka: a retrospective examination - Wijetunge, Pradeepa (My University, 2011)
The significance of information is increasing in Sri Lanka as a consequence of three development initiatives; the government is implementing many development projects in the rural sector with the objective of poverty reduction which in turn gives rise to a diversity of information needs, there are also numerous development initiatives in the service sector which raises the value of information as a commodity, in the education sector a growing emphasis is laid on resource-based independent learning which requires a highly developed library and information service in the education sector. Under these circumstances the library and information sector of Sri Lanka has an important social responsibility to satisfy the growing information needs of the Sri Lankan citizens. “The library’s role is to inform, entertain, enlighten, educate, empower and equip individuals and communities with tools enabling better life orientation, enabling communities to reorganise their social roles both knowingly and responsibly” (Ocholla, 2006 p.19). In the light of these developments, education for the library and information professionals needs the careful attention of the LIS educators, policy makers, employers and practitioners. This paper provides a retrospective analysis of the LIS education evolved in Sri Lanka throughout the last fifty years.